(untitled) (Medico Legal Update, 2021)
Background: Asthma is a heterogeneous disease with chronic inflammatory characteristics of the respiratory tract. (Nitric Oxide) (NO) levels increased significantly in patients with inflammation such as asthma in this study. Nitric Oxide (NO) levels in normal people and asthma patients are different, but no sputum of Nitric Oxide (NO) levels are associated with asthma control levels. Method: Thirty-patients consecutive sampling was conducted at asthma unit Dr. Soetomo Teaching Hospital Surabaya. The subjects were met the inclusion and exclusion criteria that assessed their asthma control with asthma control test (ACT) then measured by NO levels. Results: In this study, the subjects were divided into asthma control level; full-controlled was 4 subjects (13,3%), partially-controlled was 8 subjects (26,7%), and uncontrolled was 18 subjects (60,0%). The mean asthma control level was 18.3±4.2 with the lowest Asthma control test (ACT) score was 8 and the highest ACT score was 25. The mean NO sputum induction level was 92.043±29.040 ?M, with the lowest NO was 14.566 ?M and the highest NO was 138.350 ?M. The result of the statistical test showed a negative correlation significantly between NO-induced sputum level and asthma control level (p <0,05). Conclusion: The examination of NO sputum level could be used as an indicator in determining the level of asthma control.